Cuantificación de los Niveles de Ruido en Base a Mapeo en las Ferias del Cantón Saquisilí, periodo octubre 2018 – febrero 2019. - Vallejo Ronquillo, Brayan Homero (2019)
The proposed investigation is based on the measurement of the noise produced at the fairs at Saquisili canton on Wednesdays, Thursdays and Sundays, monitored during the day and night in the period October 2018 – February 2019, determining three areas of study: the first was carried out on Wednesdays with 12 monitoring points, the second on Thursdays with 27 monitoring points and the third on Sunday with 12 monitoring points, which were executed according to the geographical delimitation by plotting grids about the study area. The team used in this research was an integrative sonometer that allowed to measure for 10 minutes, based on the fluctuating noise methodology established in the 4.1.2.4 numeral of the book VI Annex 5 of the TULSMA and for the analysis and comparison of results with the environmental regulations in force established in table 1 of permissible maximum noise levels according to the use of soil, through which mixed commercial zone was used. In the results obtained during the day of the present investigation, it was shown that 41 points do not comply with the current environmental regulations and in night time it was evident 38 points that if they comply with the current environmental regulations, determining the timetable daytime as the greatest source of noise generation in Saquisili canton trade fairs. In the elaboration of the noise pollution maps we worked with the software ArcGIS 10.2 in which we proceeded to geo referencing the place of study and to process all the data obtained in the monitoring as they are coordinates and decibels. The noise maps showed the sonority index existing in the trade fairs in Saquisili canton, being thus the first investigation present in the zone in order to have information of this magnitude in the canton.